Comparative study of polymeric nanoparticles and traditional agents in dental implant decontamination - Håvard J Haugen; Jaime Bueno; Badra Hussain; Raquel Osorio; Mariano Sanz (Journal of Applied Biomaterials & Functional Materials)
Peri-implant diseases, such as peri-implantitis, affect up to 47% of dental implant recipients, primarily due to biofilm formation. Current decontamination methods vary in efficacy, prompting interest in polymeric nanoparticles (NPs) for their antimicrobial and protein-specific cleaning properties. This study evaluated the efficacy of polymeric nanoparticles (NPs) in decontaminating titanium dental implants by removing proteinaceous pellicle layers and resisting recontamination. Titanium discs were treated with saline water, PrefGel ® , hydrogen peroxide (H 2 O 2 ), GUM ® Paroex ® , or polymeric NPs, and analysed using SEM, EDX, XPS, and contact angle measurements to assess changes in surface composition, morphology, and hydrophilicity. Polymeric NPs significantly reduced nitrogen levels compared to PrefGel® (mean reduction: 2.6%, p  < 0.05), indicating effective protein removal. However, their carbon reduction efficacy was similar to that of other agents. SEM images revealed that polymeric NPs disaggregated larger protein aggregates but did not fully decontaminate the surface. Contact angle analysis showed changes in hydrophilicity consistent with other treatments. Hydrogen peroxide performed best overall, achieving the lowest carbon levels post-recontamination (mean reduction: 13%, p  < 0.01). While polymeric NPs exhibited unique protein-specific cleaning potential, their overall performance was comparable to traditional agents. Residual contaminants, including carbon and oxygen, persisted on all treated surfaces, indicating enhanced cleaning strategies were needed. These findings highlight the potential of polymeric NPs as an innovative approach to implant decontamination, particularly for protein-specific biofilm control. However, their efficacy in broader applications remains like that of conventional methods. This research contributes to developing targeted decontamination protocols to manage peri-implant diseases and improve long-term implant outcomes.